Lithium Metal Anodes: Graphitic Carbon Nitride Induced Micro‐Electric Field for Dendrite‐Free Lithium Metal Anodes (Adv. Energy Mater. 7/2019). Issue 7 (14th February 2019) - Lu, Ziyang; Liang, Qinghua; Wang, Bo; Tao, Ying; Zhao, Yufeng; Lv, Wei; Liu, Donghai; Zhang, Chen; Weng, Zhe; Liang, Jiachen; Li, Huan; Yang, Quan‐Hong
Abstract : In article number1803186, by Wei Lv, Quan‐Hong Yang, and co‐workers, the rainbow ring inside the 3D network is shown to be indicative of the micro‐electric field (MEF) induced by graphitic carbon nitride nanosheets that are used for uniform lithium nucleation and subsequent growth. The MEF serves as an electronic "tornado" with a strong attraction to capture Li ions and significantly reduces the Li nucleation overpotential.